Production of fire-retardant sound-absorbing panels from sago waste - Zainab, Ngaini; Hasnain, Hussain; Khairul Aidil Azlin, Abd Rahman; Norhaizat, S; Teng, JX; Lawai, V (Forest Research Institute Malaysia, 2013)
The accumulation of agricultural waste either in solid or liquid form causes environmental concern. In the utilisation of agricultural waste for developing sustainable construction material, cyclotriphosphazene-incorporated sago wastes as pendant groups were prepared and structurally characterised using infrared spectroscope and scanning electron microscope. The chemically-modified sago waste composite was applied with binders and developed as sound-absorbing panels. These panels are a class of organic–inorganic-based material that is fire resistant. The absorption coefficient of panels gave higher values at low (250 and 500 Hz) and medium (2000 Hz) frequencies. The panel was 51% lighter than fibreboard. The function and basic manufacturing of sound-absorbing panels were similar to other products available in the market. The panels showed excellent anti-termite properties.